Bacterial carbon dependence on freshly produced phytoplankton exudates under different nutrient availability and grazing pressure conditions in coastal marine waters. Issue 3 (10th December 2013) - Fouilland, Eric; Tolosa, Imma; Bonnet, Delphine; Bouvier, Corinne; Bouvier, Thierry; Bouvy, Marc; Got, Patrice; Le, Emilie; Mostajir, Behzad; Roques, Cécile; Sempéré, Richard; Sime‐Ngando, Télesphore; et al.
Abstract The effects of grazing pressure and inorganic nutrient availability on the direct carbon transfer from freshly produced phytoplankton exudates to heterotrophic bacteria biomass production were studied in Mediterranean coastal waters. The short‐term incorporation of 13C (H13CO3) in phytoplankton and bacterial lipid biomarkers was measured as well as the total bacterial carbon production (BP), viral lysis and the microbial community structure under three experimental conditions: (1) High inorganic Nutrient and High Grazing (HN + HG), (2) High inorganic Nutrient and Low Grazing (HN + LG) and (3) under natural in situ conditions with Low inorganic Nutrient and High Grazing (LN + HG) during spring. Under phytoplankton bloom conditions (HN + LG), the bacterial use of freshly produced phytoplankton exudates as a source of carbon, estimated from 13C enrichment of bacterial lipids, contributed more than half of the total bacterial production. However, under conditions of high grazing pressure on phytoplankton with or without the addition of inorganic nutrients (HN + HG and LN + HG), the 13C enrichment of bacterial lipids was low compared with the high total bacterial production. BP therefore seems to depend mainly on freshly produced phytoplankton exudates during the early phase of phytoplankton bloom period. However, BP seems mainly relying on recycled carbon from viral lysis and predators under high grazing pressure.